Detection of water quality in crayfish ponds with IoT - Abdurrasyid Abdurrasyid; Indrianto Indrianto; Meilia Nur Indah Susanti; Yudhi S. Purwanto (Institute of Advanced Engineering and Science, 2021)
Data from the Central Bureau of Statistics shows that during the first quarter of 2014 to 2019, the tendency of Indonesian crayfish export increases by an average of 3.54% in 2019 and reach 7.09 million USD. This number still fails to meet the global market demand caused by poor water quality due to cultivators’ lack of experience and education. Two parameters measured in water quality are temperature and pH. Thus, a device was made using IoT to maintain those conditions in order to increase the viability of the crayfish in the pond. The perceptron method is used to classify water quality based on those parameters. To send the data, ESP8266 is used as an intermediary for Arduino and cloud server. The result is that the information about the ponds’ condition can be seen via a smartphone. The method gives a value of 98.06% accurate in determining water quality.